Analysis of Financial Literacy, Income and Premium on Millennials’ Purchase Intention of Life Insurance Product - Djoni, Kevin; Rahardjo, Deny (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Since the beginning of the Covid-19 pandemic outbreak in the early 2020 which affects almost every country, the number of death tolls has reached up to 4.55 million. Besides deaths, the virus itself also causes fatal health problems to the patients which might cost them a large amount of money in order to be treated at the hospital or simply to purchase the necessary medicine at the pharmacy. By owning life insurance products, people will not be required to spend as much money as they should have if they do not possess any life insurance products. This purpose of this study is to determine and prove whether insurance premium, income and financial literacy do have a positive relationship on the purchase intention of life insurance products. The methodology used in this research is quantitative where the samples are gathered using an online questionnaire and processed using the variance-based structural equation modelling. From the result of the processed data, it is proved that insurance premium, income and financial literacy do not only have positive but also significant relationship on the purchase intention of life insurance products.